إكراه المتهم على الاعتراف في القانون الأفغاني من منظور الشريعة الإسلامية = Coercion of the accused to confess in Afghan law from the perspective of Islamic Sharia - Nesar, Muneer Ahmad; Laeba, Muhammad; Negasi, Mohamed Ibrahim (MIH Training and Consultancy Services and Al Hikmah Research and Publication Centre, 2025)
The study examines the issue of coercing the accused to confess in Afghan law and its compatibility with the principles of Islamic Sharia and international human rights standards, considering the legal and practical challenges. It aims to analyze the stance of Islamic Sharia and Afghan law on forced confessions and assess the extent to which Afghan legislation aligns with Islamic principles and international human rights conventions. The research adopts a comparative analytical methodology by examining legal and Sharia texts and analyzing the practical applications of these provisions within the Afghan legal system. Its significance lies in highlighting the guarantees of criminal justice in Afghanistan, strengthening the protection of defendants' rights, and providing recommendations that contribute to the development of the legal system to ensure justice in accordance with Islamic principles and international standards